Identification of impactful imaging biomarker: Clinical applications for breast and prostate carcinoma - Bäuerle, Tobias; Dietzel, Matthias; Pinker, Katja; Bonekamp, David; Zhang, Kevin S.; Schlemmer, Heinz-Peter; Bannas, Peter; Cyran, Clemens C.; Eisenblätter, Michel; Hilger, Ingrid; Jung, Caroline; Schick, Fritz; Wegner, Franz; Kiessling, Fabian (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Background Imaging biomarkers are quantitative parameters from imaging modalities, which are collected noninvasively, allow conclusions about physiological and pathophysiological processes, and may consist of single (monoparametric) or multiple parameters (bi- or multiparametric).Method This review aims to present the state of the art for the quantification of multimodal and multiparametric imaging biomarkers. Here, the use of biomarkers using artificial intelligence will be addressed and the clinical application of imaging biomarkers in breast and prostate cancers will be explained. For the preparation of the review article, an extensive literature search was performed based on Pubmed, Web of Science and Google Scholar. The results were evaluated and discussed for consistency and generality.Results and Conclusion Different imaging biomarkers (multiparametric) are quantified based on the use of complementary imaging modalities (multimodal) from radiology, nuclear medicine, or hybrid imaging. From these techniques, parameters are determined at the morphological (e. g., size), functional (e. g., vascularization or diffusion), metabolic (e. g., glucose metabolism), or molecular (e. g., expression of prostate specific membrane antigen, PSMA) level. The integration and weighting of imaging biomarkers are increasingly being performed with artificial intelligence, using machine learning algorithms. In this way, the clinical application of imaging biomarkers is increasing, as illustrated by the diagnosis of breast and prostate cancers.Key PointsCitation FormatHintergrund Bildgebungsbiomarker sind quantitative Parameter aus bildgebenden Modalitäten, welche nicht-invasiv erhoben werden und Aussagen über physiologische und pathophysiologische Abläufe zulassen, wobei diese aus einzelnen (monoparametrisch) oder mehreren Parametern (bi- bzw. multiparametrisch) bestehen können.Methode Die vorliegende Übersichtsarbeit soll den Stand der Technik zur Quantifizierung von multimodalen und multiparametrischen Bildgebungsbiomarkern vorstellen. Hierbei wird die Nutzung von Biomarkern mittels künstlicher Intelligenz thematisiert und die klinische Anwendung von bildgebenden Biomarkern bei Mamma- und Prostatakarzinomen erläutert. Für die Anfertigung des Übersichtsartikels wurde basierend auf Pubmed, Web of Science und Google Scholar eine ausführliche Literaturrecherche durchgeführt. Die Ergebnisse wurden hinsichtlich Stimmigkeit und Allgemeingültigkeit ausgewertet und diskutiert.Ergebnisse und Schlussfolgerung Die Quantifizierung von unterschiedlichen bildgebenden Biomarkern erfolgt aus der Nutzung komplementärer Bildgebungsmodalitäten (multimodal) radiologischer und nuklearmedizinischer Techniken bzw. von Hybridverfahren. Aus diesen Techniken werden Parameter auf morphologischer (z. B. Größe), funktioneller (z. B. Vaskularisierung oder Diffusion), metabolischer (z. B. Glukosestoffwechsel) und molekularer (z. B. Expression des Prostataspezifischen Membranantigens, PSMA) Ebene bestimmt. Die Integration und Wichtung von bildgebenden Biomarkern erfolgt zunehmend mit der künstlichen Intelligenz, wobei Algorithmen des maschinellen Lernens genutzt werden. Auf diesem Wege nimmt die klinische Anwendung von bildgebenden Biomarkern zu, was anhand der Diagnostik von Mamma- und Prostatakarzinomen erläutert wird.Kernaussagen Zitierweise
Keywords: quantification; artificial intelligence; imaging; breast cancer; prostate cancer; biomarker